The impact of curcumin supplementation on inflammatory processes and recovery in athletes - Rosińska-Lewandoska, Dominika; Lewandowska, Dominika; Morawska, Maria; Jarosz, Kinga; Wolff, Anna; Kożuchowska, Klaudia; Gruszka, Szymon; Szewczyk, Marcelina; Pilarz, Dawid; Ufnal, Julia (Journal of Education, Health and Sport, 2024)
Introduction Athletes frequently encounter inflammation and muscle damage due to rigorous physical activities. These physiological processes, while necessary for adaptation, can delay recovery and hinder performance if excessive. Curcumin, a polyphenolic compound derived from turmeric, is recognized for its potent anti-inflammatory and antioxidant properties. This review examines the influence of curcumin supplementation on athletic recovery and inflammation, considering its mechanisms and applications. Materials and Methods A systematic literature review was conducted using PubMed and Google Scholar, incorporating 31 studies that included randomized controlled trials, meta-analyses, and experimental research. The keywords used were "curcumin," "inflammation," "recovery," and "athletic performance." Analysis of the Literature Curcumin’s efficacy in reducing inflammation is linked to its ability to inhibit nuclear factor kappa B (NF-κB) and suppress pro-inflammatory cytokines like TNF-α and IL-6. Its antioxidant action neutralizes reactive oxygen species and upregulates antioxidant enzymes. These effects lead to reductions in muscle damage biomarkers, such as creatine kinase and lactate dehydrogenase, and improved recovery times. Advances in bioavailability through formulations like curcumin-piperine complexes enhance its practical applications in sports. Conclusions Curcumin offers significant benefits for managing inflammation and enhancing recovery in athletes. Although challenges such as low bioavailability remain, advancements in delivery methods present practical solutions. Future research should focus on long-term outcomes and optimal dosing.